Blood Donation as a Form of Social Solidarity - Hendra, Hendra; Bakari, Yulianti; Hapsa, Hapsa; Aepu, Siti Hajar N (Journal of Universal Community Empowerment Provision, 2024)
This community service topic will analyze blood donation as an act of social solidarity. This community service discusses the motivation behind blood donation and how it creates social bonds among students across universities in Palu City. The method used in this community service is a motivational intervention to donate blood through social media and through social networks by utilizing the social capital that has been built by involving various agencies. Community service in the form of blood donation activities that were carried out encountered obstacles and successes in its implementation due to internal and external factors, therefore the sustainability of the community service program continues to be carried out to build a better network of solidarity and humanity.